A novel Bi2S3/KTa0.75Nb0.25O3 nanocomposite with high efficiency for photocatalytic and piezocatalytic N2 fixation. Issue 22 (1st June 2021) - Chen, Lu; Dai, Xiaoquan; Li, Xiaojing; Wang, Junfeng; Chen, Huafong; Hu, Xin; Lin, Hongjun; He, Yiming; Wu, Ying; Fan, Maohong
Abstract : A Bi2 S3 /KTa0.75 Nb0.25 O3 (KTN) nanocomposite was synthesized via a two-step hydrothermal method and first applied in piezo-/photocatalytic N2 fixation. Abstract : A novel Bi2 S3 /KTa0.75 Nb0.25 O3 (KTN) heterojunction nanocomposite was prepared through a simple two-step hydrothermal method and primarily applied in photocatalytic and piezocatalytic N2 fixation. Bi2 S3 closely adhered to the surface of KTN nanorods and mainly acted as electron trappers to capture the photogenerated electrons in the composite, which promotes the spatial separation of photogenerated charge carriers greatly. Thus, Bi2 S3 /KTN exhibited good performance in photocatalytic N2 reduction to NH3 . Besides the high photocatalytic performance in photocatalysis, Bi2 S3 /KTN also performed well in piezocatalytic N2 fixation. The remarkable piezoelectric properties of KTN are a key factor. The added Bi2 S3 can extend the lifetime of the negative charges generated by the piezoelectric effect, thereby improving the catalytic reaction performance. This work demonstrates the great potential of Bi2 S3 /KTN in photo/piezocatalytic N2 fixation.